The behaviour of the solutions of the forced Van der Pol equation with small parameters - Ismail, Mat Rofa (Universiti Pertanian Malaysia, 1988)
The forced Van der Pol equation x+ u.(x 2 - l)x + x = p(t), jJ. > 0,1 p(t)1 ~ k where u and k are small parameters, is investigated in the phase plane, It is shown that the solutions of the equation are eventually confined in an annulas as t increases for certain values of u and k